Methodological approaches to determining the border of the suburban zone of the city of Odessa - Олійник, Валентина Дем’янівна; Стаднікова, Наталія Володимирівна (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2020)
The purpose of this paper is aimed at defining the border of the suburban zone behind economic approaches and leveling (comparing) the results with certain borders in the General plan. The development of suburban areas is one of the elements of the transformation of the economy of the city and region, determines the pace of their development. Though even today there is no common point of view on the interpretation of the concept of "suburban zone", there is no clear distinction between the definitions of "suburb", "suburban territory", "suburban area". In addition, it is important to define the boundaries of the city and suburban area, since cities tend to "expand" and "capture" adjacent territories. The boundaries of cities change significantly, which requires a corresponding study of the boundaries of the suburban zone, thus, the topic of work is re-levant. Methodology. The article considers options for delineating borders according to existing legislative acts that define the outer border of the suburban zone of large cities with an isochronous 45-60-minute accessibility by public transport to the city. In addition, the analysis of research and publications of scientists made it possible to identify other approaches to determining the boundaries of the suburban zone and compare the results with the specified border of the suburban zone in the General plan of Odessa. Thus, calculations were made and the results were visualized, using the ArcGIS Pro software, several options for determining the boundaries of the suburban zone of the city of Odessa, namely: a methodological approach was applied to calculate the population concentration index, the results of which confirmed our assumptions about the concentration of the population in the suburban zone to the place of employment, study, cultural and social development. The second methodological approach is the calculation of the gravitational model based on the distance parameter. The results allowed us to conclude that accessibility of localities to the city center is crucial. In the third approach, using the gravity model of Kareem that combines distance and demographic potential centers of research, defines the borders of suburban zone of the city of Odessa, which are maximally correlated with the specified bounds in the General plan. Practical significance. Therefore, the conducted research makes it possible to assert that one of the important indicators in determining the border of a suburban zone is the temporary isochrone, that is accessibility to the city, which, in most cases, forms a multidimensional relationship between the city and the suburban zone. The delimitation of the borders of suburban areas of cities will allow for targeted planning of the territory, organization of an effective management system, establishment of geographical features of the city development, use of the suburban territorial resources for urban development, and the relationship between the development of the city and its suburban zone. The city center and its suburban area are interconnected objects of spatial planning documentation at the stages of development of master plans for localities.